Coating Effect Condition on the Corrosion Properties of Mild Steel Substrate - Y., Mohd Yuhazri; A.R., Jeefferie; I.P, Haeryip Sihombing; O., Nooririnah; A.R, Warikh (Centre for Promoting Ideas, USA, 2011)
Corrosion is a one of problem encountered in steel industry and there are much of prevention and solution ideas applied and proposed by researches and engineers in order to avoid this problem from occurring in the future. In this research, the corrosion prevention of the mild steel is through the treatment process by the tin electroplating process. The trial and prepared specimens are addressed to the before and after corroded forms in which the surface testing is carried out through several processes such electroplating, electroplating process with various coating parameters, determination of thickness coating, as well as surface morphology examination. To determine the corrosion rate based on Tafel extrapolation, the observation is by using the scanning electron microscope. The standard measurement for tin electroplating, surface preparation, and corrosion rate is according to the ASTM B545, ASTM B183, and ASTM G102, respectively, whereas the parameters of process are regarding to the current density of coating, times and constant of solution bath. Based on the result, the best parameter finding of current density is at 6 A/dm² and 10 minutes of coating time. This parameter is capable to give a less of corrosion rate in both conditions of coatings, which is scratched coating and unscratched coating. In addition, by the lower of current density promotes the formation of tin whiskers and thin of coating but it gives a less of corrosion rate. The higher of current density promotes formation of cracking and worst of corrosion rate.